Avaliação da capacitação da equipe de enfermagem para o cuidado com cateter enteral - Gleke, Manoela Machado (2016)
People suffering from chronic illness or even acute whose oral nutrition is impossible, may require use of a catheter introduced in nose or oral cavity which reaches the gastrointestinal tract, called enteral catheter (EC). From the moment that the nurse insert this catheter into the patient, it takes several maintenance care to remain to remain as long as necessary without risk of obstruction or inadvertent removal. The introduction of this catheter is a private task of the nurse, according to COFEN Resolution (Federal Nursing Council) number 0453/2014 and needs care throughout the proceedings. The survey, through indicators, noted the continuing occurrence of loss of EC in the Intensive Care Unit of a public hospital in the state of São Paulo. From there, it was applied a training course with the nursing staff through the realistic simulation as a teaching and learning methodology. Objectives: To measure the effectiveness of training for EC conservation, to identify the theoretical knowledge of the professional previous and after the educational intervention. Method: through a quantitative approach to exploratory, the survey was traced a quasi-experimental study. As criteria for inclusion and exclusion, each professional training conducted in their working hours at a ICU bed, in order to adjust the availability of time, space and routine of the institution. Results: The final sample was composed of 54 professionals being that 14 (25.9%) nurses and 40 (74.1%) nursing technicians. The 54 participants were sufficient to test a difference in withdrawal indicator unplanned the EC equal to 16% before and 1.2% after the training; indicating (p <0.001) and established a 0.05 significance level (5%). Conclusion: The data showed that there is reliability and validity in the training of nursing staff demonstrating effectiveness in reducing the incidence of EC loss in quality indicator